DAYA HAMBAT RIZOBAKTERI KANDIDAT AGENS BIOKONTROL TERHADAP PERTUMBUHAN KOLONI PATOGEN PHYTOPHTHORA CAPSICI SECARA IN VITRO - Syamsuddin Syamsuddin; M. Abduh Ulim (Jurnal Floratek, 2013)
The utilization of biocontrol agents as an alternative to synthetic pesticides becomes widespread as the increase of awareness to negative effects of synthetic pesticides. The objectives of this research were to isolate rhizobacteria from tomato plant rhizosphere and to characterize effective rhizobacteria isolates to deter growth of Phytopthora capsici colony. The rhizobacteria was isolated from healthy tomato plant rhizosphere, and then antagonism nature to pathogen was evaluated by double culture method. Deterrent ability of the rhizobacteria was measured based on resistance zone formed due to the presence of the biocontrol agents. Among 57 isolates, 18 were potential for further evaluation. Deterrent ability test of the 18 isolates resulted in 3 isolates which were very promising to be developed as biocontrol agents to control seed borne pathogens. They were RBBM36, RBBM18 and RBBM35.